Urgensi Ekstrakurikuler Pramuka dalam Membentuk Akhlakul Karimah Siswa SMAN 1 VII Koto Sungai Sariak Kabupaten Padang Pariaman - Silvi Nelfadina; Rini Rahman (AS-SABIQUN, 2022)
The purpose of this research is to find out more deeply and also to describe the urgency of Scout extracurriculars in shaping the morality of the students of SMAN 1 VII Koto Sungai Sariak. This research is a qualitative research with descriptive research type. The data of this research were obtained and collected through interview, observation, and documentation techniques. Furthermore, the data were analyzed using techniques data reduction, data display, and conclusion drawing/verificaton. Based on the research that has been done, the moral violations that occured at SMAN 1 VII Koto Sungai Sariak were speaking and being unkind and impolite, making fun of excessively, and lacking respect. In addition, there are students who are not disciplined, and are lazy at school. This is done by student who have not been active in Scout extracurriculars. Scout extracurricular implementation is very important in this school. This is because through its interesting and fun activities, as well as always conducting coaching related to Scouting’s dasa dharma and evaluating every meeting, this Scout extracurricular is very effective in shaping students morality.